Activity-dependent neuronal Klotho enhances astrocytic aerobic glycolysis. Issue 8 (August 2019) - Mazucanti, Caio H; Kawamoto, Elisa M; Mattson, Mark P; Scavone, Cristoforo; Camandola, Simonetta
Mutations of the β-glucuronidase protein α-Klotho have been associated with premature aging, and altered cognitive function. Although highly expressed in specific areas of the brain, Klotho functions in the central nervous system remain unknown. Here, we show that cultured hippocampal neurons respond to insulin and glutamate stimulation by elevating Klotho protein levels. Conversely, AMPA and NMDA antagonism suppress neuronal Klotho expression. We also provide evidence that soluble Klotho enhances astrocytic aerobic glycolysis by hindering pyruvate metabolism through the mitochondria, and stimulating its processing by lactate dehydrogenase. Pharmacological inhibition of FGFR1, Erk phosphorylation, and monocarboxylic acid transporters prevents Klotho-induced lactate release from astrocytes. Taken together, these data suggest Klotho is a potential new player in the metabolic coupling between neurons and astrocytes. Neuronal glutamatergic activity and insulin modulation elicit Klotho release, which in turn stimulates astrocytic lactate formation and release. Lactate can then be used by neurons and other cells types as a metabolic substrate.